Hydractinia angusta Hartlaub 1904 - Galea, Horia R.; Schories, Dirk (Zenodo, 2012)
Hydractinia angusta Hartlaub, 1904 (Pl. 1A–E, Fig. 2A–C) Hydractinia angusta Hartlaub, 1904: 7, pl. 4. — Naumov & Stepanjants, 1972: 35, fig. 1. — Stepanjants, 1979: 13, pl. 1 fig. 7. — Peña Cantero & Ramil, 2006: 950, fig. 2A. — Peña Cantero, 2012: 855. Hydronema angustum — Stechow, 1923: 67. — Totton, 1930: 138. — Briggs, 1939: 10. Hydractinia dendritica Hickson & Gravely, 1907: 9, pl. 2 figs 7–10. Hydronema dendriticum — Stechow, 1921: 252. — Stechow, 1923: 67, fig. F. ? Hydractinia sp. —Stepanjants, 1972: 59, fig. 4. Material examined . Stn. SHO — 16.ii.2011, Ant.09/2011 (43 m): fertile (female) colony on worm tube (MHNG- INVE-79798). Stn. ARD — 28.i.2011, Ant.11/2011 (39 m): fertile (female) colony on worm tube (MHNG-INVE- 79799). Description . Hydrorhiza an encrusting mat issued through the coalescence of the stolonal system, covered by naked coenosarc (Pl. 1C). Spines present, often continuous with each other (Pl. 1D), provided with low ridges of perisarc (Pl. 1E), open or closed at tips. Polyps dimorphic: gastro- and gonozooids. Gastrozooids up to 5 mm high in fixed material, notably longer in life (Pl. 1A); with 12–14 amphicoronate tentacles and dome-shaped hypostome. Gonozooids dwarfed, less than 0.5 mm high, and degenerate, with 1–5 tentacles, and possibly no mouth; 4–6 rounded gonophores basally, each carrying three eggs. Nematocysts: desmonemes (6.0–6.5) × (3.6–3.8) µm and microbasic euryteles (8.9–9.8) × (3.1–3.5) µm (both measured undischarged). Remarks . Totton (1930) reexamined the type of H. dendritica Hickson & Gravely, 1907 and suggested that it could reasonably be considered as conspecific with Hartlaub's (1904) species, an opinion which is followed here. Geographical distribution . Circum-Antarctic (Peña Cantero & Ramil 2006). Published as part of Galea, Horia R. & Schories, Dirk, 2012, Some hydrozoans (Cnidaria) from King George Island, Antarctica, pp. 1-21 in Zootaxa 3321 on page 2, DOI: 10.5281/zenodo.213236